Physiological stimuli necessary for muscle hypertrophy - Hayao Ozaki; Takashi Abe; Alan E. Mikesky; Akihiro Sakamoto; Shuichi Machida; Hisashi Naito (Japanese Society of Physical Fitness and Sports Medicine, 2015)
This paper reviews the existing literature about muscle hypertrophy resulting from various types of training to document the significance of mechanical and metabolic stresses, and to challenge the conventional ideas of achieving hypertrophy that exclusively rely on high-load resistance training. Low-load resistance training can induce comparable hypertrophy to that of high-load resistance training when each bout or set is performed until lifting failure. This is attributable to the greater exercise volume and metabolic stress achieved with low-load exercise at lifting failure, which, however, results in a prolonged exercise bout. Endurance exercises (walking and cycling) at moderate intensity are also capable of eliciting muscle hypertrophy, but at much slower rates (months rather than weeks) in limited muscle or age groups. Blood flow restriction (BFR) in working muscles, however, accelerates the development of metabolic fatigue, alleviating the time consuming issue associated with low-load or endurance training. These alternative training methods, however, cannot completely replace conventional high-load resistance training, which provides superior strength gain as well as performance improvement even for trained individuals. The alternative approaches, therefore, may be considered for those who are less enthusiastic or under certain medical conditions, or who have limited or no access to proper equipment. However, people should be aware that low-load resistance training or endurance training entails substantial effort and/or discomfort at lifting failure or with BFR. Understanding the advantages and disadvantages of each method will help in assigning the most suitable training program for each client's goals and needs.